'Let's talk about sex': a patient‐led survey on sexual function after colorectal and pelvic floor surgery. (22nd March 2021) - Dames, Nicola B.; Squire, Sarah E.; Devlin, Anthony B.; Fish, Rebecca; Bisset, Carly Nichola; Tozer, Phil; ,
Abstract: Aim: Discussions regarding sex after colorectal and pelvic floor surgery are often overlooked by clinicians. This is the first patient designed and delivered study to explore sexual function and practices after colorectal surgery. The aim was to explore the questions about sex that matter to patients and their partners following colorectal or pelvic floor surgery through a patient and public involvement survey. The results of this work will underpin the creation of a sex patient reported outcome measure. Methods: An anonymous online survey tool (Survey Monkey™) was disseminated via social media (Twitter, Facebook). Thematic analysis was applied to 130 free text comments posted by participants to identify key themes. Results: Some 632 individuals completed the survey. Most respondents were women (80% n = 507), 49.5% ( n = 312) were married and 14% ( n = 87) identified as LGBT+ (lesbian, gay, bisexual and transgender +). Indications for surgery varied: 34% were treated for ulcerative colitis ( n = 214); 31% Crohn's ( n = 196); 17% ( n = 109) cancer; and 17% ( n = 110) for perianal fistula. For patients who had a stoma formed (85%, n = 540), over half (51%, n = 324) lived with their stoma for 1–5 years. Respondents reported substantial alterations to their preferences for sexual positions, sexual activity and body confidence following surgery. Most respondents indicated that they were not offered advice about sex by a healthcare professional. Conclusions: The survey showed a substantial impact on the mechanics of sex following colorectal surgery. Few patients were offered preoperative information regarding sex, which has implications for informed consent. This study demonstrates a clear unmet need, voiced by patients, that open dialogue is necessary preoperatively to discuss sexual (dys)function.